DISTINGUISH AMONG SOME SELECTIVE WATERMELONS BY USING ISSR TECHNOLOGY - Elias, M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experiment conducted Using 12 primers related to ISSR technology in distinguishing among the 21 selective back to the three variety of watermelon they are each of the selective Crimson Sweet which code to W1, W2, W3 and W4 and the variety Sugar Baby which coded to SH1 ,SH2 ,SH3 ,SH4 ,SH5,SH6 and SH7 and the variety Charleston Gray which is coded to G1 ,G2,G3 ,G4 ,G5 ,G6 ,G7 ,G8, G9 and G10 . The results showed that the primers used gave 89 total bands were all of the polymorphism was 100%. Found that the primers 810, 840 and 864 were high ability of the way to give it the highest numbers of bands while the primers 808 and 834 of the ability of the few by giving them fewer bands. 9 primers able to give distinct bands for some selective, which distinguishes them from the rest of the other primers. The results showed that the principles component analysis ( PCA) for the variety Crimson Sweet correlation the selective W1 and W2  while W3 not correlation with  W4  or with each other,  and correlation SH1 , SH3 and SH6 with each other apart from the SH4 , SH7 , SH2 and SH5 in the variety Sugar Baby as to the selective of Charleston Gray has divided into two groups, the first group included five selective G7 , G5 ,G6, G4 and G8  apart from the second group, which included five selective  G1 , G2 , G3 , G9 and G10. . And it found that the high genetic distance between the two varieties Charleston Gray and Sugar Baby. Therefore the primers ISSR showed that the variance between the communities by variance of arrangement of nucleotide. It can be concluded the possibility of the use of biotechnology in breeding programs.